Heat Exchanger Network (HEN) Analysis of The Power Plant Industry Using Aspen Energy Analyzer Software - Maktum Muharja; Arief Widjaja; Rizki Fitria Darmayanti; Bramantyo Airlangga; Rendra Panca Anugraha; Mar'atul Fauziyah; Eko Wijanarto; Mohammad Sholehuddin; Achri Isnan Khamil (ASEAN Journal of Chemical Engineering, 2023)
Heat recovery is considered as the key to improve energy efficiency in the process design. An appropriate heat exchanger network (HEN) design is an effective tool to maximize heat recovery from the process streams and to minimize energy consumption. The objectives of this study were arranging optimum HEN based on the annual cost in the power industry. HEN in the Paiton Steam Power Plant, East Java, Indonesia, was designed using spreadsheet and Aspen Energy Analyzer with Peng-Robinson equation. Pinch analysis was conducted by comparing Tmin (10°C - 19°C) to obtain Maximum Energy Recovery (MER) and Heat Exchanger Area (HEA). The HEN design was optimized using grid diagram. Simulation in this study succeeded to reduce the annual cost the most effectively at ∆Tmin 16°C. This design optimized the process integration and contributed to the capital, operation, and total annual cost reduction of 14.3%. The maximum energy recovery was 286,706 kW and HEA 138.790 m2. This result is a solution for Steam Power Plant as an effort for enhancing energy efficiency and the company competitiveness.